Medidas antropométricas según sexo en nacidos a término y pretérmino en el Hospital Regional Docente de Trujillo durante 2005-2015 - Aguilar Mantilla, Amar Ismael (2017)
To determine the anthropometric measures according to the gender of the term and preterm infant at the Regional Teaching Hospital of Trujillo during 2005-2015. Methodology: A cross-sectional descriptive study was carried out on the anthropometric measures (weight, length and cephalic perimeter) of the preterm and term groups that met the selection criteria; the measures were evaluated by gender, by group and by each gestational week. Data were obtained from the database of the Neonatology service of the HRDT, and the clinical histories with incomplete information were physically reviewed. The Chauvenet´s statistical criterion was used to eliminate the "outliers". Results: A significant difference (p <0.001) was found, according to gender, in each anthropometric measure analyzed in the group of term births ([37-42 weeks>). In the group of preterm infants ([28-37 weeks>) no significant difference by gender was found for any anthropometric measure analyzed. Conclusion: The minimum and maximum values, the mean and the percentiles of the weight, length and cephalic perimeter of the term and preterm infants did not differ significantly from the values reported in the reviewed literature